Evaluasi Waktu Start Up pada Proses Peruraian Limbah Stillage secara Anaerobik Menggunakan Reaktor Fluidized Bed Kontinyu dengan Zeolit sebagai Media Imobilisasi - Kunthi Widhyasih; Wiratni Budhijanto; Chandra W Purnomo (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Stillage is wastewater from the ethanol industry. Organic matter content in the stillage is quite high, so it can damage to the environment if disposed of directly into the environment. Stillage has great potential to produce biogas that can be converted into energy by anaerobic treatment process. One of the anaeobic digestion methods is the bacterial cell immobilization technique. One of the  reactor types using cell immobilization technique is Anaerobic Fluidizied Bed Reactor (AFBR). This study uses a set of AFBR reactor containing zeolite media with particle diameters of 0.5 - 0.8 mm and operated at a fluidization level (FL) 20% - 40% of the total effective volume of the reactor. This work studied the effect initial organic concentrations and time dring start up process on decomposition of stillage using AFBR. Scope of this work was evaluating AFBR performance  by comparing the matematical model simulation result with experimental data. The simulation results were used as standard, that described AFBR performance under ideal conditions. This esperiment was conducted for 57 days in two cycles with varied sCOD concentrations and was done in batch recirculation process. The experiment showed that initial organic concentration was affected start up process.  On high organic concentration, start up process failed, but the maximum concentrations limits have not  been determined yet. Experiment showed that charging  50.000 mg sCOD/L to the reactor have made the system failed due the organic shock loading and inhibiton by VFA. Optimum time of start up was determined in first cycle, with initial organic concentration 10.000 mg sCOD/L. Optimum time of start up is 7 until 10 days. If start up process was longer than 10 days, bacteria entered the decay phase due insufficiency of substrat. AFBR performance evaluation using mathematical approaches produced more objective and more accurate result, although there were several factor not evaluated in the mathematical model such as the inhibition effect. These results could be used as a reference for reactor performance optimization especially in addressing the problem of inhibition